Cap polyposis–an unusual cause of diarrhoea. Issue 4 (April 1993) - Campbell, A P; Cobb, C A; Chapman, R W; Kettlewell, M; Hoang, P; Haot, B J; Jewell, D P
Abstract : 'Cap polyposis' is a poorly recognised condition with distinct clinical, sigmoidoscopic, and pathological features that may be confused with other inflammatory conditions of the large intestine including pseudomembranous colitis and idiopathic chronic inflammatory bowel disease. The pathogenesis is unknown but on the basis of the characteristic histological appearances, which are similar to those seen in situations where mucosal prolapse is the underlying mechanism, it has been suggested that the latter may be an important aetiological factor. Two cases are described. Histological features in the first (presence of intramucosal elastin) and clinical features in the second (rectal prolapse) support the above hypothesis.